Analytical models for load capacities of variable thickness reinforced concrete slabs considering compressive membrane action and boundary effects. (1st November 2021) - Zhu, Ying-Jie; Zhou, Meng; Zhu, Jian-Min; Nie, Xin
Highlights: Analytical methods for load capacities of laterally restrained slabs are proposed. Effects of boundary conditions and slab depth variation are considered. Proposed methods are validated by finite element analysis and tests. Effects of design parameters on the compressive membrane action are revealed. Abstract: The lateral restraint eccentricity and rotational restraint stiffness significantly influence the compressive membrane action (CMA) in reinforced concrete slabs. However, these two factors have rarely been studied and no analytical model considering them has been established. In addition, most analytical methods for evaluation of CMA were derived for slabs with constant thickness, even though slabs with variable depth are quite common in practice. Therefore, this paper develops analytical methods to predict the load capacities of laterally restrained slabs considering the effects of lateral restraint eccentricity, rotational restraint stiffness, and slab depth variation. Based on the compatibility conditions and equilibrium of forces, the axial forces and bending moments can be derived by solving equations as long as the deflection at the load application point is provided. Then the corresponding load can be determined and the load capacity of the slab can be obtained by iterative calculations. The proposed methods are then validated by comparing to finite element analysis and four groups of test results, in which the effects of lateral restraint eccentricity, rotational restraint stiffness, and slab depth variation are explicitly reflected. Finally, comprehensive parametric analyses are conducted by using the proposed models. The interaction effects of the design parameters on the CMA are revealed for slabs with strong and weak rotational restraints, respectively.